Cyclic AMP-dependent protein kinase regulates transcription of the phosphoenolpyruvate carboxykinase gene but not binding of nuclear factors to the cyclic AMP regulatory element. - Quinn, P G (1990)
We have examined the binding of factors in rat liver nuclear extracts to the phosphoenolpyruvate carboxykinase (PEPCK) gene cyclic AMP (cAMP) response element (CRE) and other CREs and have isolated a rat liver CRE-binding protein (CREBP) cDNA. In addition, we have examined the influence of altering the phosphorylation state of nuclear factors on both CRE binding and in vitro transcription. Specific binding to the PEPCK CRE was measured in a mobility shift assay. CRE sequences of the PEPCK, somatostatin, and glycoprotein hormone alpha subunit genes competed equally for binding of rat liver nuclear factors to the PEPCK CRE, whereas mutant PEPCK CRE sequences did not compete for binding. Oligonucleotides complementary to rat pheochromocytoma CREBP (Gonzalez et al., Nature [London] 337:749-752, 1989) were used to prime rat liver and brain cDNA in the polymerase chain reaction. The predominant CREBP molecule obtained was identical to the rat pheochromocytoma CREBP except for a 14-amino-acid deletion in the N-terminal half that was also present in a human placental cDNA (Hoeffler et al., Science 242:1430-1433, 1988). The regulation of transcription by cAMP was examined by coincubation of rat liver nuclear extract with the purified catalytic subunit of cAMP-dependent protein kinase (protein kinase A). Although binding to the CRE was unaffected, in vitro transcription directed by the PEPCK promoter was stimulated by catalytic subunit, and this effect was blocked by protein kinase inhibitor peptide. In contrast, when nuclear extract was coincubated with phosphatase, there was substantial inhibition of in vitro transcription directed by the PEPCK promoter, but there was no effect on binding to the CRE. The major effects of catalytic subunit were exerted through the CRE, but residual stimulation was evident in promoter fragments containing only the TATA element. These data suggest that factors are bound to the CRE at constitutively high levels and that their capacity for transcriptional activation is regulated by phosphorylation.